2020
DOI: 10.3201/eid2609.190592
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Carbapenemase-Producing Enterobacteriaceae Carriage in Hospital Patients

Abstract: R apid global dissemination of carbapenemaseproducing Enterobacteriaceae (CPE) poses a public health threat (1). To prevent the spread of CPE in healthcare settings, international guidelines advocate for early identification, isolation, and contact precautions (2,3). To provide information helpful for the design of rational infection control policies, we estimated CPE carriage duration in a hospital cohort and identified risk factors for prolonged carriage.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 8 publications
0
19
0
2
Order By: Relevance
“…Leveraging the observation that CPE carriage in hospital patients can be resolved within 3 months, with 98.5% probability within a year for our cohort 24 (though other cohorts have reported longer durations 25,26 ), we tracked gut microbiome composition in this cohort of individuals for a year to understand ecological changes associated with decolonization (up to 12 timepoints, 361 samples in total; Table 1, Supplementary File 1 ). Specifically, stool samples were obtained from hospital patients who screened positive for CPE carriage (n=29, index subjects), as well as their non-CPE-colonized family members (n=17, serving as home environment-matched controls) and characterized via deep shotgun metagenomic sequencing (>50 million Illumina 2×100bp reads, on average; Methods ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Leveraging the observation that CPE carriage in hospital patients can be resolved within 3 months, with 98.5% probability within a year for our cohort 24 (though other cohorts have reported longer durations 25,26 ), we tracked gut microbiome composition in this cohort of individuals for a year to understand ecological changes associated with decolonization (up to 12 timepoints, 361 samples in total; Table 1, Supplementary File 1 ). Specifically, stool samples were obtained from hospital patients who screened positive for CPE carriage (n=29, index subjects), as well as their non-CPE-colonized family members (n=17, serving as home environment-matched controls) and characterized via deep shotgun metagenomic sequencing (>50 million Illumina 2×100bp reads, on average; Methods ).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, stool samples were obtained from hospital patients who screened positive for CPE carriage (n=29, index subjects), as well as their non-CPE-colonized family members (n=17, serving as home environment-matched controls) and characterized via deep shotgun metagenomic sequencing (>50 million Illumina 2×100bp reads, on average; Methods ). Principal coordinates analysis with average-linkage clustering based on taxonomic profiling of the data showed that there are multiple distinct community configurations (I, II, III, IV), where CPE positive samples (based on stool culture and qPCR 24 ) were less commonly seen in configurations I and II, and more commonly seen in configurations III and IV ( Figure 1a, Supplementary Figure 1, Supplementary File 2 ). This statistically significant shift of CPE positive samples along PCoA1 (Wilcoxon rank-sum p-value<1.4×10 −8 , Supplementary Figure 2a ) is defined by a gradient of relative abundances that are most strongly correlated for the genera Escherichia (negative i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Transient or intermittent patient carriage of CPOs could also be a contributing factor. 34 It is also important to note that a complex interplay of factors can affect carbapenemase-mediated carbapenem resistance, including plasmid and carbapenemase gene copy numbers, as well as alterations in the promoter regions of carbapenemase genes. For instance, Kitchel et al 35 reported that increased bla KPC gene expression levels coupled with dual porin loss in Klebsiella pneumoniae isolates led to the highest minimum inhibitory concentrations to carbapenem antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Although CPOs were not recovered from a subset of carbapenemase gene‐positive specimens in our PPS, this is likely due to the high sensitivity of the PCR assays that were performed in combination with a low colonizing burden of CPOs in patients, limiting recovery by culture. Transient or intermittent patient carriage of CPOs could also be a contributing factor 34 . It is also important to note that a complex interplay of factors can affect carbapenemase‐mediated carbapenem resistance, including plasmid and carbapenemase gene copy numbers, as well as alterations in the promoter regions of carbapenemase genes.…”
Section: Discussionmentioning
confidence: 99%
“…Gut colonization often precedes and serves as a reservoir for transmission to other body sites resulting in the development of subsequent infections [ 13 ]. The duration of gut colonization with multi-drug resistant (MDR) bacteria, such as carbapenem-resistant K. pneumoniae varies from 43 to 387 days [ 14 ].…”
Section: Introductionmentioning
confidence: 99%